POTENSI DAN PELUANG PENGELOLA BENIH SUMBER KEDELAI DI PROVINSI JAMBI - Yardha Yardha; Julistia Bobihoe (Jurnal Agroekoteknologi, 2020)
The activity aimed to produce and disseminate Anjasmoro variety soybean seed sources, increase the ability and capacity of breeder farmers in producing soybean source seeds and disseminate the New Superior Varieties (VUB) of soybean Agricultural Research and Development Agency. The activity was carried out at the Harapan Mulya farmer group, Dusun Baru Village, VII Koto District, Tebo Regency, Keltan Suka Jaya, Village Suo-suo Kec. Sumay, Tebo Regency and Sido Makmur Keltan, Simpang Village, Kacamatan Berbak, Tanjung Jabung Timur Regency from January to December 2019. The soybean seed multiplication activities are carried out in a participatory manner in collaboration with farmers from planning, implementation to initial evaluation and processing so farmers understand each stage of captivity activities. The data collected consists of secondary and primary data. Qualitative data were analyzed descriptively, while quantitative data were analyzed with variance. Financial feasibility analysis of seed production is carried out through Revenue per Cost (R / C.) The results of the study found that: SS class soybean seed production carried out in Tebo District with an area of 41 hectares obtained seed production of 43.5 tons, and in Tanjung Jabung Timur District with an area of 10 hectares obtained seed production of 7.5 tons, improved farmers' knowledge and skills in seed propagation technology, and improved institutional soybean seed breeding.